Features of the organization of the accounting in the state unitary organizations (case study Government institution – the Pension Fund of the Russian Federation) - Kanaeva A. V. (Interactive science, 2017)
this article studies characteristics of the organization and staging of accountancy in the state unitary organization with specific reference. It describes the tasks of accounting, accounting functions and duties of the chief accountant. The paper explores the structure of accounting in general. А special attention is paid to one of the accounting departments – Department for settlements with individuals and payments to the budget. The functions and duties of ordinary accountant of the Department are described in detail.
Keywords: accounting; бухгалтерское дело; структура бухгалтерской службы; обязанности главного бухгалтера; государственная унитарная организация; accounting service structure; accounting functions; duties of the chief accountant; the state unitary organization